Estudio y viabilidad del potencial energético solar en las zonas rurales de Barrancabermeja, para el desarrollo de fuentes de generación eléctrica fotovoltaica (2023)
The purpose of this degree project is to be able to determine the capacity of solar energy use of the city of Barrancabermeja and its rural areas. Through research and evaluation of the performance of the incidence of the sun in the city and its surrounding areas, it will be possible to indicate the best options that allow opening a panorama of possibilities in the region, in this way, the scenario can be structured and adjusted. of development that will make it possible to achieve an effective development of this source of clean energy, thus leveraging the use and implementation of renewable energies, which have the potential to provide solutions to energy needs and that serve as tools with the aim of reducing the effect that is generated in the natural environment, as well as the dependence on fossil fuels.